Economic evaluation of pig rearing fed with different level of jaggery filter cake along with concentrate (Indian Journal of Animal Production and Management, 2018)
The cost of balanced ration was estimated by considering the prevailing prices of the feed ingredients,  mineral salt, common salt and vitablend. The relative cost effectiveness of each diet was thus assessed.  Further, the amount incurred for treatment of any disease outbreak was also included in the expenditure  under different groups. By considering the total live weight gain under each treatment, the cost involved  to produce 1 kg live weight gain was calculated. Net profit for each treatment was calculated separately  by considering the sale price of pork produced at the end of experiment. The total cost during the whole  experiment was highest in group I (no JFC), followed by group II, group IV and group III and lowest in  group V (ad. lib JFC with no concentrate). Cost involved for production of 1 kg live weight for group I to  V was Rs 35.25, 32.34, 29.48, 29.42 and 19.31, respectively. High cost incurred in group I was due to  sole concentrate feeding and lowest cost in group V was due to sole feeding of JFC, respectively. Cost  involved in group IV was marginally higher as compared to group III due to relatively more concentrate  intake along with known quantity of JFC.
Keywords: Concentrate; Economics; Jaggery Filter Cake; Pig; Profit